The effect of rapid maxillary expansion in children: a meta-analysis - Santana, Denise M.C. [UNESP]; Nogueira, Vania S. [UNESP]; Lima, Silvana A.M. [UNESP]; Fernandes, Luciana P.A. [UNESP]; Weber, Silke A.T. [UNESP] (Elsevier, 2021)
Introduction: Craniofacial growth is modified by chronic mouth breathing. Rapid maxillary expansion leads to separation of the mid-palatal suture, improving the occlusion and the upper airway size. Aim: Systematically evaluate scientific articles on the effects of rapid maxillary expansion on airway dimensions and classify the quality of the evidence of the information. Methods: Searches on PUBMED, LILACS, EMBASE, SCOPUS, WEB OF SCIENCE and COCHRANE, as well as in the grey literature were performed. The articles found were selected and evaluated both for the risk of bias (ROBINS-I) and for the quality of evidence (GRADE). Results: Of the 309 works found, 26 papers were selected for full reading, of which 22 were excluded. Data compilation and analysis were performed in four papers, two being controlled non-randomized clinical trials and two non-randomized and uncontrolled clinical trials. No randomized clinical trial was found. Conclusions: The meta-analysis found an increase in the internasal and inter-zygomatic distances and oropharyngeal volume after rapid maxillary expansion, which, together with clinical findings, makes the recommendation favorable to the intervention. The quality of the evidence for each outcome was considered very low.
Keywords: Children; Meta-analyses; Mouth breather; Rapid maxillary expansion; Transverse maxillary deficiency